The experience of grandparenting: between vital compensation, paradoxes, emotional dilemmas and intergenerational conflicts - Alba Lucía Marín-Rengifo; María Cristina Palacio-Valencia (Prospectiva, 2015)
Grandparenting is the participation of grandparents in the processes of upbringing or care for their grandchildren, either in a central or peripheral manner. Being preceded by the proper exercise of maternity and paternity, this experience requires revealing the emotional connotation given by the contemporary familistic ideology in order to highlight the paradoxes and emotional dilemmas that provide the intergenerational conflicts with content. This view involves the background of a social imaginary around spoiling kids but with a vital compensation component in the distinction between upbringing and care. Here lies the meaning of crossing times in the process of upbringing and caring for the younger generation.